Safety for the Rhinologist in the Age of COVID-19: Mask Use, Nasal Corticosteroids, Saline Irrigation, and Endoscopic Procedures – Literature Review - Kosugi, Eduardo Macoto; Villa, Jonatas Figueiredo; Ramos, Henrique Faria; Luz-Matsumoto, Gabriela Ricci; Serrano, Thiago Luis Infanger; Campos, Carlos Augusto Correia de; Barreto, Carolina Cincurá; Lima, Clara Mônica; Fornazieri, Marco Aurélio; Piltcher, Otavio; Lessa, Marcus Miranda; Romano, Fabrizio Ricci (International Archives of Otorhinolaryngology, 2022)
Introduction Coronavirus disease 2019 (COVID-19) has claimed millions of lives. Adequate protection of the professionals involved in patient care is essential in the battle against this disease. However, there is much uncertainty involving safety-relarted topics that are of particular interest to the rhinologist in the context of COVID-19.Objective To evaluate the current evidence regarding three safety-related topics: mask and respirator use, performance of nasal endoscopic procedures, and use of topical nasal and intranasal medications (saline irrigation and nasal corticosteroids).Methods A literature review was performed on the PubMed, Scopus, and Cochrane databases, with standardized search queries for each of the three topics of interest.Results In total, 13 articles on mask use, 6 articles on the safety of nasal corticosteroids, 6 articles on the safety of nasal endoscopic procedures, and 1 article on nasal irrigation with saline solution were included in the final analysis.Conclusion N95 respirators are essential for the adequate protection of otolaryngologists. If reuse is necessary, physical methods of sterilization must be employed. No evidence was found to contraindicate the use of nasal corticosteroids, whether acute (in the management of sinonasal inflammatory conditions) or continued (in patients who use them chronically). Nasal irrigation with saline solution apparently does not increase the risk in the context of COVID-19. Nasal endoscopic procedures should only be performed after testing the patient for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and the surgical team must wear full personal protective equipment to prevent aerosol exposure.
Keywords: COVID-19; safety; corticosteroids; masks; nasal saline solution; nasal endoscopy